2014
DOI: 10.1590/s1677-5538.ibju.2014.02.16
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection is not related with prostatitis-related symptoms: results from a case-control study

Abstract: ARTICLE INFO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…25 In this study, the distribution of HPV genotypes in co-infected men confirmed the increased circulation of the genotypes LR-HPV42 and HR-HPV51 especially among young people, as recently emerged from other Italian surveys. 10,26 Recently, Perino et al 27 reported that couples who underwent assisted reproductive technology cycles experienced an increased risk of pregnancy loss when HPV DNA testing was positive in the male partner, compared with non-infected patients. The HR-HPV51 and HR-HPV52 were the genotypes most frequently identified in the male partner of infertile couples.…”
Section: Discussionmentioning
confidence: 99%
“…25 In this study, the distribution of HPV genotypes in co-infected men confirmed the increased circulation of the genotypes LR-HPV42 and HR-HPV51 especially among young people, as recently emerged from other Italian surveys. 10,26 Recently, Perino et al 27 reported that couples who underwent assisted reproductive technology cycles experienced an increased risk of pregnancy loss when HPV DNA testing was positive in the male partner, compared with non-infected patients. The HR-HPV51 and HR-HPV52 were the genotypes most frequently identified in the male partner of infertile couples.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that exposure to environmental factors such as infectious agents and dietary carcinogens, and hormonal imbalances lead to injury of the prostate gland and to the development of chronic inflammation and regenerative ‘risk factor’ lesions, referred to as proliferative inflammatory atrophy (PIA) 65 .Two meta-analyses with the statistically significant evidence of the association between prostatitis and prostate cancer 66 67 also suggest that inflammation resulting from infections may be one mechanism for prostate cancer carcinogenesis. Although a case-control study has showed that HPV infections are not related with prostatitis-related symptoms when urethral swab was used for HPV detection 68 , another study has showed that HPV was identified in the prostatic secretions from patients with type III prostatitis and might be associated with the degree of intraprostatic inflammation 69 . Whether HPV infections associated with the risk of prostate cancer is mediated by chronic prostatic inflammation which leads to initiation and progression of prostate cancer, needs further functional research.…”
Section: Discussionmentioning
confidence: 99%
“…Based on meta-analyses of 21 studies by Zhang et al, there is a correlation and enhanced risk between prostatitis leading to benign prostate hyperplasia and finally prostate cancer [87]. Multiple pathogenic organisms including high risk HPVs have been identified in prostatic secretions and semen of patients with prostatitis [88][89][90][91]. The biology underlying inflammation and cancer is complex particularly if infectious agents such as HPVs are involved.…”
Section: Human Papillomavirus Prostatitis Benign Prostate Hyperplasmentioning
confidence: 99%